Keberhasilan Program MBG dalam Perspektif Manajemen Rantai Pasok: Peran Moderasi Keterlibatan UMKM terhadap Pertumbuhan Ekonomi Lokal - Mochammad Haris Firdaus; J E Sutanto (SAFE-Network, 2026)
This study aims to analyze the impact of supply chain management on the success of the Free Nutritious Food Program (MBG), with the involvement of SMEs as a moderating variable. The research approach used is a quantitative approach with a Likert scale 1-5 questionnaire survey administered to 290 SME actors involved in the MBG supply chain in Jombang Regency. The collected data was then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that supply chain management has a positive and significant impact on the success of the MBG program, while the involvement of SMEs also shows a positive and significant influence on the program's success. Furthermore, the involvement of SMEs has been proven to moderate the relationship between supply chain management and the success of the MBG program, highlighting that a high level of SME involvement can strengthen the effectiveness of supply chain management in achieving program goals. These findings indicate that effective supply chain management and active SME participation are crucial factors that mutually support the success of MBG program implementation, which in turn can promote inclusive local economic growth.